2021
DOI: 10.1016/j.amjcard.2021.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Utility of Culprit SYNTAX Score in Patients With Cardiogenic Shock Complicating ST-Segment Elevation Myocardial Infarction

Abstract: A higher SYNTAX score (SS) is strongly associated with poor prognosis in patients with cardiogenic shock complicating ST-segment elevation myocardial infarction (CS-STEMI). However, the predictive value of culprit-lesion SYNTAX score (cul-SS) and SS has not been compared although the culprit-lesion-only primary percutaneous coronary intervention (PCI) strategy showed improved long-term survival recently. This study compared the predictive utility of cul-SS and SS for in-hospital mortality among the patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Failure to recanalize, suboptimal outcomes, distal embolization, noreflow, and impaired myocardial perfusion are some of the unresolved difficulties that frequently arise during PCI in patients with a high intracoronary thrombus burden, indicating an unmet need (19,20). In the high target lesion SYNTAX score lesions receiving balloon predilation, a maximum predilation pressure >10 atm was associated with a higher risk of noreflow (21).…”
Section: Discussionmentioning
confidence: 90%
“…Failure to recanalize, suboptimal outcomes, distal embolization, noreflow, and impaired myocardial perfusion are some of the unresolved difficulties that frequently arise during PCI in patients with a high intracoronary thrombus burden, indicating an unmet need (19,20). In the high target lesion SYNTAX score lesions receiving balloon predilation, a maximum predilation pressure >10 atm was associated with a higher risk of noreflow (21).…”
Section: Discussionmentioning
confidence: 90%
“…In the study published by Kyehwan Kim et al during the writing phase of our study, for the first time, the cul-SS was compared with the SYNTAX score and evaluated in cardiogenic shock patients presenting with STEMI. In that study, the cul-SS was found to be superior to the SYNTAX score in terms of the predictive power of in-hospital mortality rates [17]. The population of their study consisted of patients with myocardial infarction presenting with cardiogenic shock.…”
Section: Discussionmentioning
confidence: 95%